In Situ Morphology Studies of the Mechanism for Solution Additive Effects on the Formation of Bulk Heterojunction Films. Issue 3 (29th September 2014) - Richter, Lee J.; DeLongchamp, Dean M.; Bokel, Felicia A.; Engmann, Sebastian; Chou, Kang Wei; Amassian, Aram; Schaible, Eric; Hexemer, Alexander
<x xml:space="preserve">Abstract</x> The most successful active film morphology in organic photovoltaics is the bulk heterojunction (BHJ). The performance of a BHJ arises from a complex interplay of the spatial organization of the segregated donor and acceptor phases and the local order/quality of the respective phases. These critical morphological features develop dynamically during film formation, and it has become common practice to control them by the introduction of processing additives. Here, in situ grazing incidence X‐ray diffraction (GIXD) and grazing incidence small angle X‐ray scattering (GISAXS) studies of the development of order in BHJ films formed from the donor polymer poly(3‐hexylthiophene) and acceptor phenyl‐C61‐butyric acid methyl ester under the influence of two common additives, 1, 8‐octanedithiol and 1‐chloronaphthalene, are reported. By comparing optical aggregation to crystallization and using GISAXS to determine the number and nature of phases present during drying, two common mechanisms by which the additives increase P3HT crystallinity are identified. Additives accelerate the appearance of pre‐crystalline nuclei by controlling solvent quality and allow for extended crystal growth by delaying the onset of PCBM‐induced vitrification. The glass transition effects vary system‐to‐system and may be correlated to the number and composition of phases present during drying.